The nature of anhedonia and avolition in patients with first-episode schizophrenia. Issue 2 (14th October 2015) - Lui, S. S. Y.; Liu, A. C. Y.; Chui, W. W. H.; Li, Z.; Geng, F.; Wang, Y.; Heerey, E. A.; Cheung, E. F. C.; Chan, R. C. K.
Abstract : Background: Patients with schizophrenia have intact ability to experience emotion, but empirical evidence suggests that they fail to translate emotional salience into effortful behaviour. Previous research in patients with chronic schizophrenia suggests that working memory is important in integrating emotion and behaviour. This study aimed to examine avolition and anhedonia in patients with first-episode schizophrenia and clarify the role of working memory in emotion–behaviour coupling. Method: We recruited 72 participants with first-episode schizophrenia and 61 healthy controls, and used a validated emotion-inducing behavioural paradigm to measure participants' affective experiences and how experienced emotion coupled with behaviour. Participants were given the opportunity to expend effort to increase or decrease their exposure to emotion-inducing photographs. Participants with schizophrenia having poor working memory were compared with those with intact working memory in their liking and emotion–behaviour coupling. Results: Patients with first-episode schizophrenia experienced intact 'in-the-moment' emotion, but their emotion was less predictive of the effort expended, compared with controls. The emotion–behaviour coupling was significantly weaker in patients with schizophrenia with poor working memory than in those with intact working memory. However, compared with controls, patients with intact working also showed substantial emotion–behaviour decoupling. Conclusions: Our findings provide strong evidence for emotion–behaviour decoupling in first-episode schizophrenia. Although working memory deficits contribute to defective translation of liking into effortful behaviour, schizophrenia alone affects emotion–behaviour coupling.